2010
DOI: 10.1123/ijsc.3.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Sports Coverage in Israel: Perception Versus Reality

Abstract: With a focus on the question of public interest, the study investigated editing considerations of women's sports coverage in written daily newspapers in Israel. To examine sports readers' views regarding the coverage of women in sports sections, and to compare them with the views of sports editorial boards, a representative survey was conducted among male and female readers of sports columns and among male and female sports writers responsible for coverage. The research findings indicate a lack of connection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Many countries, including Israel, have legislation regarding women's representation on the boards of their sport organizations (Galily and Betzer-Tayar, 2014;Tamir and Galily, 2010;Zach and Adiv, 2015). However, inequalities and barriers to progress still exist.…”
Section: Encouraging Insightsmentioning
confidence: 99%
“…Many countries, including Israel, have legislation regarding women's representation on the boards of their sport organizations (Galily and Betzer-Tayar, 2014;Tamir and Galily, 2010;Zach and Adiv, 2015). However, inequalities and barriers to progress still exist.…”
Section: Encouraging Insightsmentioning
confidence: 99%
“…Studies that have indicated similarities between the sporting and military experience (Tamir & Bernstein, 2013; Tamir & Galily, 2010) have emphasized the national role played by both institutions. 7 The notion that both the military and national sports teams go “to battle” on behalf of the country automatically and implicitly assumes a banding together of the nation around the national flag, while its representatives are off “in combat,” fighting for the country.…”
Section: Resultsmentioning
confidence: 99%
“…Sports is a broad cultural phenomenon that affects all strata of society and plays an important role in the social lives of most societies in the world (Tamir and Galily, 2010). More than merely entertainment for the masses, sports is effectively a ''religion'' with hundreds of millions of global believers (Price, 2001).…”
Section: Literature Review Sports and Societymentioning
confidence: 99%